A meta‐analysis of mother–child synchrony in respiratory sinus arrhythmia and contextual risk. Issue 1 (16th December 2022) - Miller, Jonas G.; Armstrong‐Carter, Emma; Balter, Leah; Lorah, Julie
Abstract: Biobehavioral frameworks of attachment posit that mother–child dyads engage in physiological synchrony that is uniquely formative for children's neurobiological, social, and emotional development. Much of the work on mother–child physiological synchrony has focused on respiratory sinus arrhythmia (RSA). However, the strength of the existing evidence for mother–child RSA synchrony during interaction is unclear. Using meta‐analysis, we summarized results from 12 eligible studies comprising 14 samples and 1201 children ranging from infancy to adolescence ( M age = 5.68 years, SD = 4.13, range = 0.4–17 years) and their mothers. We found that there was a statistically significant, albeit modest, positive within‐dyad association between mother and child fluctuations in RSA. There also was evidence for significant heterogeneity across studies. Less mother–child RSA synchrony was observed in high‐risk samples characterized by clinical difficulties, history of maltreatment, or socioeconomic disadvantage. We did not find that mother–child RSA synchrony significantly differed by task context, mean child age, or by epoch length for computing RSA. Collectively, these findings suggest that mother–child dyads show correspondence in their fluctuations in RSA, and that RSA synchrony is disrupted in high‐risk contexts. Future directions and implications for the study of parent–child physiological synchrony are discussed.